A phenome-wide association study of a lipoprotein associated phospholipase A2 loss-of-function variant in 90 000 Chinese adults - Millwood, I; Bennett, D; Walters, R; Clarke, R; Waterworth, D; Johnson, T; Chen, Y; Yang, L; Guo, Y; Bian, Z; Hacker, A; Yeo, A; et al. (Oxford University Press, 2016)
Background Lipoprotein-associated phospholipase A2 (Lp-PLA2) has been implicated in development of atherosclerosis, however, recent randomised trials of Lp-PLA2 inhibition reported no beneficial effects on vascular diseases. In East Asians, a loss-of-function variant in the PLA2G7 gene can be used to assess the effects of genetically-determined lower Lp-PLA2. Methods PLA2G7V279F (rs76863441) was genotyped in 91 428 individuals randomly-selected from the China Kadoorie Biobank of 0.5M participants recruited in 2004-2008from 10 regions of China, with seven years follow-up. Linear regression was used to assess effects of V279F on baseline traits. Logistic regression was conducted for a range of vascular and non-vascular diseases, including 41 ICD-10 coded disease categories. Results PLA2G7V279F frequency was 5% overall (range 3-7% by region), and 9,691 (11%) participants had at least one loss-of-function variant. V279F was not associatedwith baseline blood pressure, adiposity, blood glucose, or lung function. V279F was not associated with major vascular events (7141 events; OR=0.98 per F variant, 95% CI 0.90-1.06), or other vascular outcomes, including major coronary events (922 events; 0.96, 0.79-1.18) andstroke (5967 events; 1.00, 0.92-1.09). Individuals with V279F had lower risks of diabetes (7031 events; 0.91, 0.84-0.98) and asthma (182 events; 0.53, 0.28-0.98), but there was no association after adjustment for multiple testing. Conclusions Lifelong lower Lp-PLA2 activity was not associated with major risks of vascular or non-vascular diseases in Chinese adults. Using functional genetic variants in large-scale prospective studies with linkage to a range of health outcomes is a valuable approach to inform drug development and repositioning.